Rabbit-assisted interventions in a Greek kindergarten - LOUKAKI (Κ. ΛΟΥΚΑΚΗ) K.; KOUKOUTSAKIS (Π. ΚΟΥΚΟΥΤΣΑΚΗΣ) P. (Journal of the Hellenic Veterinary Medical Society, 2017)
Objective of the study was to confirm efficacy of intervention by means of a rabbit. We studied and recorded reactions of pupils and personnel in the presence of a rabbit in a comprehensive-type kindergarten. We selected a group of 39 clinically healthy pupils, 2.5- to 4-year-old, who were attending the kindergarten and used relevant weighted questionnaires for pupils and teachers. In the presence of the animal, pupils’ ability of socializing, communicating and expressing emotions increased significantly. Teachers also found the results of the intervention particularly positive. It is concluded that rabbit intervention in a public kindergarten is feasible, low cost and does not require specialized personnel. The rabbit is a popular animal, familiar to children, hence the intervention was successful and effective as similar interventions with dogs, providing the chance to children to learn and become accustomed to animals.